Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Chen, Jia-Wei; Shao, Jun-Jie; Zhao, Shao-Fei; Lu, Pei-Heng; Li, Si-Yu; Yuan, Hao; Ma, Peng-Wei; Lun, Yu-Qiang; Wang, Wei-Long; Liang, Rui; Gao, Wei; Yang, Qian; et al. (Environmental science and pollution research international, 2023)
Genetic factors play an important role in susceptibility to noise-induced hearing loss (NIHL). Alternative splicing (AS) is an essential mechanism affecting gene expression associated with disease pathogenesis at the post-transcriptional level, but has rarely been studied in NIHL. To explore the role of AS in the development of NIHL, we performed a comprehensive analysis of RNA splicing alterations by comparing the RNA-seq data from blood samples from NIHL patients and subjects with normal hearing who were exposed to the same noise environment. A total of 356 differentially expressed genes, including 23 transcription factors, were identified between the two groups. Of particular note was the identification of 56 aberrant alternative splicing events generated by 41 differentially expressed genes between the two groups, with exon skipping events accounting for 54% of all the differentially alternative splicing (DAS) events. The results of functional enrichment analysis showed that these intersecting DAS genes and differentially expressed genes were significantly enriched in autophagy and mitochondria-related pathways. Together, our findings provide insights into the role of AS events in susceptibility and pathogenesis of NIHL.